Analysis of 3D production process. - Tan, Han Kiong. (2011)
The group set out on making a comedy short film in 3D, drawing inspiration from hand drawn animation such as Bugs Bunny for our gags. The project is also an attempt to develop an understanding of the workflow in a 3D production pipeline. The animated short film produced is titled ‘Do Not Disturb!’ In this report, the production process will be described and explained briefly. Critical evaluation of the achieved results will be followed by the learning outcome of this project.